1997
DOI: 10.1002/(sici)1096-9888(199702)32:2<209::aid-jms466>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Immonium Ions in the Fragmentation of Protonated Peptides

Abstract: The pathways leading to the formation of immonium (An) ions in the fragmentation of protonated peptides were investigated using metastable ion studies, including kinetic energy release measurements, and low‐energy collision‐induced dissociation studies. In addition to the established pathway Bn→An+CO, it is shown that B2 ions, in suitable circumstances, fragment directly to A1 ions. In addition, metastable ion studies show that A1 ions can be formed directly from protonated di‐ and tripeptides most likely by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
113
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 7 publications
10
113
0
Order By: Relevance
“…2, fragmentation of the doubly-protonated precursor ion results in the formation of the ion pairs b 1 /y 8 and b 2 /y 7 . An a 8 ion, which is presumably formed from the b 8 ion [39][40][41][42][43], is also observed. Because the y 8 (Fig.…”
Section: Fragmentation Of Bradykinin Ion Populations Labeled By H/d Ementioning
confidence: 99%
See 1 more Smart Citation
“…2, fragmentation of the doubly-protonated precursor ion results in the formation of the ion pairs b 1 /y 8 and b 2 /y 7 . An a 8 ion, which is presumably formed from the b 8 ion [39][40][41][42][43], is also observed. Because the y 8 (Fig.…”
Section: Fragmentation Of Bradykinin Ion Populations Labeled By H/d Ementioning
confidence: 99%
“…A much poorer match to theoretical is found for the pseudoion pair y 1 /a 8 , with the sum of the deuterium incorporations consistently slightly lower than the theoretical for most ion populations. One of the mechanisms thought to occur for the formation of an a n ion is loss of CO from the b n ion [39][40][41][42][43]. However, this mechanism does not involve hydrogen.…”
Section: Distribution Of Deuterium Atoms After Sori-cid Of the D 1 -Dmentioning
confidence: 99%
“…Statistical [19 -24] and mechanistic [25][26][27][28][29][30][31][32] analyses have led to a better understanding of peptide fragmentation behavior. Specifically, these studies have revealed residuespecific preferential cleavage N-terminal to proline (Pro), C-terminal to aspartic acid (Asp) and glutamic acid (Glu), and C-terminal to oxidized cysteine (e.g., cysteine sulfinic acid and cysteine sulfonic acid) [19,20,[33][34][35][36][37][38][39][40][41][42][43].…”
mentioning
confidence: 99%
“…Although these b n ions were initially considered to be acylium ions [8,10,11], extensive experimental and theoretical studies [14 -19] have shown that, in many cases, the b n ions have protonated oxazolone structure as shown in Scheme 2 formed by cyclization involving the carbonyl function next-nearest to the amide bond being ruptured. In several cases where there are more reactive side-chain groups in the peptide, alternative cyclic structures are formed by interaction with sidechain functionality as the amide bond cleavage occurs [20,21].Although the fragmentation reactions of b 2 ions have been studied in some detail [14,18,22,23], the fragmentation reactions of larger b ions have seen less study [15] and the fragmentation of a n ions have seen even less study. A related question is whether, for larger protonated peptides, the lower mass b ions are formed directly by fragmentation of the protonated peptide or are secondary fragmentation products.…”
mentioning
confidence: 99%
“…Although the fragmentation reactions of b 2 ions have been studied in some detail [14,18,22,23], the fragmentation reactions of larger b ions have seen less study [15] and the fragmentation of a n ions have seen even less study. A related question is whether, for larger protonated peptides, the lower mass b ions are formed directly by fragmentation of the protonated peptide or are secondary fragmentation products.…”
mentioning
confidence: 99%